Pengaruh Promosi Sosial Media Terhadap Minat Beli Pada Produk Kerajinan Di Rajapolah: (Survei Pada Calon Konsumen Pusat Kerajinan Tangan Ashika Art Rajapolah Tasikmalaya) - Fajar Rahayu (CV. ULIL ALBAB CORP, 2022)
The objectives of this study was to determine promotion social media and buying interest in Ashika Art Rajapolah Tasikmalaya Handicraft Products. As well as analyzing the effect of promotion social media on buying interest in Ashika Art Rajapolah Tasikmalaya Handicraft Products. The research method used in this study is a survey method, while the types of data used in this study are primary data and secondary data. The object of this research is the consumer of Ashika Art Rajapolah Tasikmalaya handwork center, with the sampling technique using the accidental sampling method. The data analysis technique used is simple regression analysis and hypothesis testing. The results of this test prove that promotion social media has a significant effect on buying interest in Ashika Art Rajapolah Tasikmalaya handicraft products. It is recommended that the Ashika Art Rajapolah Tasikmalaya Handicraft Center further increase promotions social media so that it can increase consumer buying interest.